PERAN GANDA PEREMPUAN BURUH TANI KARET DALAM MENINGKATKAN EKONOMI KELUARGA: (STUDI KASUS ETNIS JAWA DI DESA SIDOJADI KECAMATAN BUKIT MALINTANG KABUPATEN MANDAILING NATAL) - Hasibuan, Nadiah (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This research discusses the dual role of women rubber farming workers in improving the family economy (case study of javanese ethnicity in sidojadi village, bukit malintang district, mandailing natal regency). The research result show that having two roles in a family is not an easy thing, women are required to have a dual role in the family, being a housewife and working as a rubber farmer because they have to help support the family economy. The informants explained how they divide their time between activities both at work and in dealing with the family. The husband lack of income means that the wife has to enter the world, conflict in the family often occur due to economy problems and low education makes it difficult for female agricultural workers to find work. The theory used in this research uses role theory where role theory emphasizes the nature of individuals as social actors who study social behavior according to the position they occupy in the work environment and society. Individuals will experience conflict within themselves if two or more pressures occur simultaneously directed at a person. This research uses qualitative methods with data collection techniques such as observation, interviews and documentation. This research produces an understanding of the dual roles of women rubber farming workers.